Impactos econômicos do Simples Nacional nas microrregiões de Sergipe - Santos, Andreia Almeida dos (2016)
Micro and small enterprises have a very important role in the Brazilian economy, both in the generation of employment and income distribution. Many become the kickoff of many individuals seeking employment. The indexes show their representation in all regions of Brazil. Both the number of companies as in the concentration of GDP in the country. This work aims to analyze the performance of micro and small enterprises in the regions of Sergipe after the implementation of the National Simple by Complementary Law 123/2006, in order to compare the behavior of these companies in the 13 micro-regions. The study begins with a literature review where the importance of state intervention in an economic scenario is treated to minimize the failures of markets, the need for taxation to keep the state and guarantee subsidies to the need of the population. Brings fiscal federalism as an important part in the sharing of revenues to the poor ones. Then enter into the merits of micro and small businesses knowing their concepts and benefits targeted to them, deployments over the years of incentives for their development, such as the Simple Federal, and soon after with the National Simple and creation the Single Microentrepreneur figure. The work concludes with a comparative analysis in the regions of Sergipe, referring to the number of enterprises, employment and income. Raising important information about the role of micro and small enterprises in the less favored regions of Sergipe.